2015
DOI: 10.1002/2015jg002932
|View full text |Cite
|
Sign up to set email alerts
|

Chemical weathering and long‐term CO2 consumption in the Ayeyarwady and Mekong river basins in the Himalayas

Abstract: The role of terrestrial river systems in the global carbon cycle on a long timescale has been a subject of interest, especially in the context of past climate changes such as the global cooling in the Cenozoic. The discharges of water and carbon into the ocean from the Himalayan watersheds are among the highest in the world. However, there are few reliable geochemical data from the Ayeyarwady River. This study focused on reevaluating chemical weathering in the Himalayan watersheds based on samples taken from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In parallel, there was a general increase (Fig. 4), as also shown in other major rivers such as the Mississippi (Cai et al, 2008) and the Oubangui Mekong River, and this seems to be also the case in the Upper Mekong River (Manaka et al, 2015). TA in freshwater was also correlated to Na + but with a slope of 0.…”
Section: Mixing Modelssupporting
confidence: 51%
“…In parallel, there was a general increase (Fig. 4), as also shown in other major rivers such as the Mississippi (Cai et al, 2008) and the Oubangui Mekong River, and this seems to be also the case in the Upper Mekong River (Manaka et al, 2015). TA in freshwater was also correlated to Na + but with a slope of 0.…”
Section: Mixing Modelssupporting
confidence: 51%
“…Compared to extensive studies conducted in polluted rivers and estuaries in Europe and North America (Frankignoulle et al, 1998;Borges et al, 2006;Hartmann et al, 2007;Borges and Abril, 2011;Griffith and Raymond, 2011;Amann et al, 2012;Joesoef et al, 2015), few efforts have been made to J.-H. Park et al: Anthropogenic perturbations to carbon fluxes in Asian river systems measure pCO 2 in polluted Asian rivers, except for some large rivers and estuaries in East Asia (Zhai et al, 2005;Chou et al, 2013;Ran et al, 2015b;Yoon et al, 2017). These studies, together with a small number of studies that used water chemistry data to estimate pCO 2 levels in major Asian rivers such as the Mekong (Li et al, 2013b), the Yangtze (Ran et al, 2017b), the Ganges-Brahmaputra (Manaka et al, 2015b), and Indian estuaries (Gupta et al, 2009;Sarma et al, 2012), underscored the importance of anthropogenic OM and nutrients for riverine CO 2 dynamics, particularly along lower river reaches and estuaries draining highly populated areas. When published data on pCO 2 were compared between headwater streams and tributaries feeding into the middle and lower reaches of major Asian rivers, tributary pCO 2 levels (mean: 2116 µatm) tended be higher than those for headwaters of Asian rivers (mean: 1170 µatm; Table 3; Fig.…”
Section: Effects Of Water Pollution On Riverine Metabolisms and Co 2 mentioning
confidence: 99%
“…As summarized in Table 3, many studies of aquatic CO 2 dynamics in India have been conducted in estuaries and coastal areas (Mukhopadhyay et al, 2002;Biswas et al, 2004;Gupta et al, 2009;Sarma et al, 2012;Samanta et al, 2015), except for the secondary data on pCO 2 calculated using C system equations (Pierrot et al, 2006) and water quality data collected in various headwaters (Sarin et al, 1989;Bickle et al, 2003;Chakrapani and Veizer, 2005) and lower reaches (Manaka et al, 2015b) of the Ganges-Brahmaputra. The values of pCO 2 estimated for some headwaters, lower reaches, and tributaries of the Ganges basin (mean: 893; range: 65-2620 µatm) were relatively low compared to other Asian rivers (Table 3; Fig.…”
Section: Effects Of Water Pollution On Riverine Metabolisms and Co 2 mentioning
confidence: 99%
“…S1 in = 2 : 1). However, Li et al (2014) have shown, based on an extensive water chemistry data set, that carbonate rock weathering largely dominates silicate weathering in the Lower Mekong River, and this seems to also be the case in the Upper Mekong River (Manaka et al, 2015). TA in freshwater was also correlated to Na + but with a slope of 0.5, lower than expected from the weathering of albite (NaAlSi 3 O 8 ; HCO − 3 : Na + = 1 : 1), and to K + but with a slope of 14, higher than expected from the weathering of microcline (K-feldspar, KAlSi 3 O 8 , HCO − 3 : K + = 1 : 1).…”
Section: Data Setmentioning
confidence: 99%